Penerapan Finite State Machine pada Game 3D â€œVirus Hunterâ€ - Fridy Mandita; Bramantyo Kusumo Jati (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2022)
During the pandemic, people's space for movement is limited. The government implements the Work from Home (WFH) rule which requires everyone to work with gadgets in their respective homes. This situation makes most people frustrated with the existing limitations. Games are one of the forms of entertainment that can be done during a pandemic. In addition to entertainment, games can also be used as learning media in order to increase the level of vigilance against viruses or diseases. The Virus Hunter game is intended so that people can entertain themselves by playing and gaining insight into various kinds of viruses. This research was conducted during the stages of research and development which was then tested functionally using white box testing methods. Usability testing was carried out using the SUS method. In game design, the Non-Player Character (NPC) uses the Finite State Machine method to approach player behavior. The virus hunter game test results state that the functional application can run well and get a usability score of 75,87% in the Acceptable and Good categories in the Adjective Range. Â